Next‐generation ice core technology reveals true minimum natural levels of lead (Pb) in the atmosphere: Insights from the Black Death. Issue 4 (28th June 2017) - More, Alexander F.; Spaulding, Nicole E.; Bohleber, Pascal; Handley, Michael J.; Hoffmann, Helene; Korotkikh, Elena V.; Kurbatov, Andrei V.; Loveluck, Christopher P.; Sneed, Sharon B.; McCormick, Michael; Mayewski, Paul A.
Abstract: Contrary to widespread assumptions, next‐generation high (annual to multiannual) and ultra‐high (subannual) resolution analyses of an Alpine glacier reveal that true historical minimum natural levels of lead in the atmosphere occurred only once in the last 2000 years. During the Black Death pandemic, demographic and economic collapse interrupted metal production and atmospheric lead dropped to undetectable levels. This finding challenges current government and industry understanding of preindustrial lead pollution and its potential implications for human health of children and adults worldwide. Available technology and geographic location have limited previous ice core investigations. We provide new high‐ (discrete, inductively coupled plasma mass spectrometry, ICP‐MS) and ultra‐high resolution (laser ablation inductively coupled plasma mass spectrometry, LA‐ICP‐MS) records of atmospheric lead deposition extracted from the high Alpine glacier Colle Gnifetti, in the Swiss‐Italian Alps. We show that contrary to the conventional wisdom, low levels at or approaching natural background occurred only in a single 4 year period in 2000 years documented in the new ice core, during the Black Death ( 1349–1353 C.E.), the most devastating pandemic in Eurasian history. Ultra‐high chronological resolution allows for the first time detailed and decisive comparison of the new glaciochemical data with historical records. Historical evidence shows that mining activity ceased upwind of the core site from 1349 to 1353, while concurrently on the glacier lead (Pb) concentrations—dated by layer counting confirmed by radiocarbon dating—dropped to levels below detection, an order of magnitude beneath figures deemed low in earlier studies. Previous assumptions about preindustrial "natural" background lead levels in the atmosphere—and potential impacts on humans—have been misleading, with significant implications for current environmental, industrial, and public health policy, as well as for the history of human lead exposure. Trans‐disciplinary application of this new technology opens the door to new approaches to the study of the anthropogenic impact on past and present human health. Plain Language Summary: Current policies to reduce lead pollution in the air are based on the assumption that preindustrial levels of lead in the air were negligible, safe, or nonexistent. This trans‐disciplinary article shows that this is not the case, using next‐generation laser technology in climate science, in combination with detailed historical and archaeological records in as many as seven languages from all over Europe. We show that lead levels in the air have been elevated for the past 2000 years, except for a single 4 year period. This 4 year period corresponds with the largest pandemic ever to ravage Western Europe (the Black Death), resulting in a 40–50% reduction in population and interruption mining and smelting of lead in the European continent. This unprecedented population collapse and severe economic decline halted lead mining and smelting and related emissions of lead in the air. This trans‐disciplinary study is a collaboration between the Initiative for the Science of the Human Past at Harvard University and the Climate Change Institute at the University of Maine. It uses next‐generation technology and expertise in history, climate science, archaeology, and toxicology, brought to bear in a highly detailed contribution to planetary health, with crucial implications for public health and environmental policy, and the history of human exposure to lead. Key Points: Preindustrial, atmospheric lead (Pb) levels have been grossly underestimated, with significant implications for human health and development Overwhelming historical evidence shows that catastrophic demographic collapse caused atmospheric Pb to plummet to natural levels only once in the last 2000 years Next‐generation ice core analysis by laser ablation inductively coupled plasma mass spectrometry allows for the first time an ultra‐high resolution (subannual) record of Pb deposition